A Multivariate Statistical Analysis on Digital Divide across Asia and Oceania Countries (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of ICT acts as a catalyst for economic growth, yet, the digital disparities are presenting a threat by leaving some countries behind in the race to global competitiveness. Although numerous attempts have been made to analyze the digital gap in various regions, there hasn’t been any detailed research for the Asia and Oceania countries. The purpose of this study is to analyze and observe the evolution of the digital divide in this region. The authors tackled the measurement of the digital divide among thirty-one countries of this region using multivariate statistical methods. Factor analysis was used to determine a small number of factors that summarize the set of digital development factors. Using cluster analysis, countries were clustered into five groups and were ranked from digital laggards to digital leaders. We observed the short-term digital divide evolution by drawing the path movements of these countries between the years 2011 and 2016 which showed a clear picture of what countries have improved their digital development scores in the past five years. At last, this research suggested some recommendations for policymakers to help them narrow the digital gap between their countries and ‘digital leaders’.